2015
DOI: 10.1007/s10585-015-9720-7
|View full text |Cite
|
Sign up to set email alerts
|

Nidogen 1 and Nuclear Protein 1: novel targets of ETV5 transcription factor involved in endometrial cancer invasion

Abstract: Endometrial cancer is the most frequent malignancy of the female genital tract in western countries. Our group has previously characterized the upregulation of the transcription factor ETV5 in endometrial cancer with a specific and significant increase in those tumor stages associated with myometrial invasion. We have shown that ETV5 overexpression in Hec1A endometrial cancer cells induces epithelial to mesenchymal transition resulting in the acquisition of migratory and invasive capabilities. In the present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 30 publications
4
43
0
Order By: Relevance
“…66 Another study revealed a possible NID1 involvement in the acquisition of migratory and invasive properties by endometrial cancer cells. 67 It has also been shown that NID1 was present at high levels in the secretome of lung metastases in both breast cancer and melanoma. 68 This study showed that NID1 promoted cancer cell migration, invasion, and metastases in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…66 Another study revealed a possible NID1 involvement in the acquisition of migratory and invasive properties by endometrial cancer cells. 67 It has also been shown that NID1 was present at high levels in the secretome of lung metastases in both breast cancer and melanoma. 68 This study showed that NID1 promoted cancer cell migration, invasion, and metastases in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Reminiscent of the role of TGFβ in cancer and metastatic progression, NID1 seems to be a tumor suppressor and metastasis promoter in our breast cancer and melanoma models. However, these functions may be cancer type-dependent, as NID1 promoted tumorigenesis and metastasis of endometrial cancer (Pedrola et al 2015), while loss of expression through promoter methylation in colon and gastric cancers (Ulazzi et al 2007) or increased protein degradation in prostate cancer (Ko et al 2015) correlated with enhanced tumor growth and metastasis. One possible mechanism by which NID1 may decrease tumorigenesis could be its strong binding affinity for perlecan, which can be secreted by quiescent ECs to mute proliferative and invasive phenotypes of lung and breast cancer cells in vitro and reduce their protumorigenic and proinflammatory signaling (Franses et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We first examined its role in cell migration and invasion, processes known to be important during metastasis and previously attributed to NID1 expression in endometrial cancer (Pedrola et al 2015). Indeed, NID1 overexpression in MDA-MB-231 and HTB140 cells significantly increased transwell migration and invasion in modified Boyden chamber assays ( Fig.…”
Section: Loss Of Nid1 Expression Hampers Lung Metastatic Progression mentioning
confidence: 97%
See 1 more Smart Citation
“…3B). NUPR1 is involved in various biological functions such as apoptosis, chemotherapy resistance and endoplasmic-reticulum etc [27] and its knockdown decreases migration capability in endometrial cancer cells [12] and pancreatic cancer cells [28]. Migration data also showed concomitant data that HBx overexpressed cells have more wound healing capacity.…”
Section: Discussionmentioning
confidence: 96%